Motive Ingenieurstudierender für den Besuch (fach-)didaktischer Lehrveranstaltungen im Projekt EduTech Net OWL - Vernholz, Mats; Temmen, Katrin (die hochschullehre)

Shaping Tomorrow’s Classrooms: Integrating AI in Technology Teacher Training and VET in Germany - Vernholz, Mats; Schäfers, Johannes; Jonas-Ahrend, Gabriela; Temmen, Katrin (Smart Technologies for an All-Electric Society. STE 2025. Lecture Notes in Networks and Systems)

From Time-Saving to Skill-Building: Reframing Generative AI for Lesson-Planning—A Conceptual Design Paper - Vernholz, Mats; Sims, Craig; Treagust, David (Education Sciences)

Different Pathways, Shared Challenges: Reflections on Entering Vocational Teaching in Germany - Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin
Germany is experiencing a shortage of teachers, a situation that is particularly evident in the domain of technical vocational education. In response to this, various pathways into vocational teacher education have been established. These pathways are diverse in their nature but all lead to the same teacher degree as traditional teacher education. In two interview studies (n=22 (pre service) vocational teachers), initial motives of entering teacher education (based on FIT-Choice) as well as retrospective views on the career choice after entering the profession (based on PLP model) are analyzed. The present study compares the reflective views of pre-service teachers and career-changing in-service teachers (CCIT). Although both groups generally perceive their career choice positively, the results raise questions about why CCITs did not enter the field of teacher education in the first place. Additionally, the analysis allows for further discussion about existing teacher education programs in times of teacher shortage.
Keywords: vocational teacher education; teacher shortage; career-changing teachers; teacher reflections

Shifting Minds or Reinforcing Myths? Empirical Insights into AI-related Affective Changes Among Future Technology Teachers - Vernholz, Mats; Schäfers, Johannes; Jonas-Ahrend, Gabriela; Temmen, Katrin

„Und ich sag mal, Theorie und Praxis ist zweierlei“. Wie können Praxisphasen Lehramtsstudierende auf zukünftige Anforderungen vorbereiten? - Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin (Zukünfte technischer Bildung)

Why Engineering Students Choose a Career in Teacher Education – Qualitative Analysis of Bachelor Students' Motives - Vernholz, Mats; Temmen, Katrin (Towards inclusive and egalitarian vocational education and training: Key challenges and strategies from a holistic and multi-contextual approach. Proceedings of the 6th Crossing Boundaries Conference in Vocational Education and Training)

Vom Prompt zur Praxis – Kooperatives Seminarkonzept zur KI-gestützten Unterrichtsentwicklung in der gewerblich-technischen Lehramtsausbildung - Schäfers, Johannes; Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin

Vergleichsprozesse und ihr Einfluss auf die selbst wahrgenommenen Fähigkeiten angehender gewerblich-technischer Lehrkräfte - Vernholz, Mats; Temmen, Katrin (Book of Abstracts zum 8. Technikdidaktik-Symposium)

Im Spannungsfeld zwischen Fach- und Bildungswissenschaft - Einflussfaktoren auf die Selbsteinschätzungen gewerblich-technischer Lehramtsstudierender in den verschiedenen Bereichen des Master of Education - Vernholz, Mats; Temmen, Katrin

Uni trifft Schule - Kooperative Unterrichtsentwicklung unter Einbezug von KI in der gewerblich-technischen Lehramtsausbildung - Vernholz, Mats; Schäfers, Johannes; Jonas-Ahrend, Gabriela; Temmen, Katrin

„Und ich sag mal, Theorie und Praxis ist zweierlei” – Wie können Praxisphasen Lehramtsstudierende auf zukünftige Anforderungen vorbereiten? - Vernholz, Mats; Jonas-Ahrend, Gabriela

Gewerblich-technische Lehrkräftebildung in Deutschland - Analyse der Einflüsse auf das akademische Selbstkonzept von Lehramtsstudierenden technischer (beruflicher) Fachrichtungen - Vernholz, Mats (Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2024)

Academic self-concepts of pre-service technology teachers for vocational education in Germany according to the TPACK- Model - Vernholz, Mats (Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity)

Teaching Technologies: Continuous Interplay Between Educational and Industrial Advances - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Teacher Education in the Wake of Covid-19)
The field of teaching technologies is in constant interplay between educational and industrial advances. Since the beginning of the twenty-first century, digitalization and automatization have become increasingly important. In industrial and social life, we see similar fast-moving developments. These factors challenge education, specifically vocational education, greatly, and raise two very different, yet very much connected questions: how to prepare students for their vocational lives and how to prepare teachers to communicate the necessary competencies to their students? This chapter provides an overview of advances, challenges, and possible solutions, focusing on the three key fields of vocational education in Germany: Industry 4.0, Education 4.0, and innovative teacher education. Most importantly, however, the text examines the continuous interplay between and among these fields. The beginning of the chapter is dedicated to vocational teacher education, in accordance with industrial and educational advances. Specifying this, characteristics of Industry 4.0, as well as students' and teachers' perceptions of Industry 4.0, are discussed. This is followed by an introduction to the concept of so-called learning factories as a possible way of integrating aspects of Industry 4.0 in German vocational schools. The end of the chapter is dedicated to the required changes in educational settings today and in the future. Though Industry 4.0, Education 4.0, and innovative teacher education are each widely discussed in the current literature, the interplay of all three fields reveals a research gap. This chapter tries to close this gap and provide an important contribution to the research field.

Gewerblich-technische Lehrkräftebildung in Deutschland – Analyse der Einflüsse auf das akademische Selbstkonzept von Lehramtsstudierenden technischer (beruflicher) Fachrichtungen - Vernholz, Mats; Temmen, Katrin

Wie bewährt sich das duale berufliche Ausbildungssystem der industriellen Metall und Elektroausbildung unter Pandemiebedingungen? Lehrkräfte und Auszubildende reflektieren - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s): Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)

Industrie 4.0 in der beruflichen Bildung – Automatisierter Maschinenbaulernbetrieb Paderborn - Vernholz, Mats